2007
DOI: 10.2139/ssrn.1002387
|View full text |Cite
|
Sign up to set email alerts
|

How Strong is the Case for Downward Real Wage Rigidity?

Abstract: This paper explores the existence of downward real wage rigidity (DRWR) in 19 OECD countries, over the period 1973-1999, using data for hourly nominal earnings at the industry level. Based on a nonparametric statistical method, which allows for country-and yearspecific variation in both the median and the dispersion of industry wage changes, we find evidence of some DRWR in OECD countries overall, as well as for specific geographical regions and time periods. There is some evidence that real wage cuts are less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 44 publications
3
13
0
Order By: Relevance
“…Indeed, our data show a negative correlation between wage cuts across countries and the percentage of workers covered by collective agreements (see also Figure 1). This is in line with results on the frequency of wage cuts in industry data across countries reported by Holden and Wulfsberg (2009).…”
Section: Survey Design and Data Descriptionsupporting
confidence: 92%
“…Indeed, our data show a negative correlation between wage cuts across countries and the percentage of workers covered by collective agreements (see also Figure 1). This is in line with results on the frequency of wage cuts in industry data across countries reported by Holden and Wulfsberg (2009).…”
Section: Survey Design and Data Descriptionsupporting
confidence: 92%
“…In contrast, several studies have found empirical evidence for the existence of considerable downward real wage rigidity in a number of OECD countries (see Christofides and Li, ; Bauer et al ., ; Dickens et al ., ). Furthermore, Holden and Wulfsberg () have found support for some DRWR in the same industry data. In view of the problem of distinguishing between real and nominal downward rigidity, we would also expect that some of the rigidity that we find might, in fact, be caused by real rigidity.…”
Section: Estimates Of Dnwrmentioning
confidence: 88%
“…Together with (11), (12) determines the perceived elasticities of prices with respect to wages on the part of wage setters under the two monetary regimes and different wage bargaining arrangements.…”
Section: Monetary Policymentioning
confidence: 99%
“…From Table 3, it is straightforward to derive under what conditions interior solutions with a 12 Similarily, if the tradables sector is wage leader and this sector is the larger, i.e. 1 − γ > 1 2 , then the critical value is again negative (first row, second column in Table 5).…”
Section: Potential Interior Solutions With a Higher Wage For The Follmentioning
confidence: 99%
See 1 more Smart Citation